Tangential continuity of the curvature tensor at grain boundaries underpins disclination density determination from spatially mapped orientation data. (January 2019) - Fressengeas, C.; Beausir, B.
Abstract: Tangential continuity at grain boundaries confers to the curvature tensor smoothness properties needed for the determination of the components of the disclination density tensor available from the orientation maps provided by electron backscattered diffraction measurements. The smoothness implied by attributing a gradient status to the curvature tensor is overachieving and leads to uniformly vanishing disclination density fields. We detail the appropriate field representations for the rotation and curvatures built from the discrete orientation data sets, as well as the relevant numerical differentiation procedures. Illustrations are provided by using both simple constructed data sets and actual measurements.